ANALYSIS OF JUDGES' CONSIDERATIONS IN SETTLING MUSYARAKAH AGREEMENT DISPUTES - prasheila kusmastuti, ines; Al Muazzami, Al Muazzami (Universitas Muhammadiyah Surabaya, 2024)
Judges in deciding cases of sharia economic dispute resolution must consider sharia principles such as the DSN Fatwa. In fact, there are still decisions that do not consider sharia principles even though the case handled is a musyarakah contract financing dispute. This research method is normative to examine the judge's consideration in resolving musyarakah contract financing disputes. The secondary data of this research was obtained through literature study and analyzed descriptively qualitatively. The results of this study are that the legal rules used by judges are incomplete. Judges who should apply sharia principles do not use DSN Fatwas such as DSN Fatwa No. 08/DSN-MUI/ IV/2000 concerning Musyarakah Financing and DSN Fatwa No. 42/DSN-MUI/VIII/2004 concerning Ta'widh as a consideration. The nominal ta'widh charged to the defendant was also deemed inappropriate due to the absence of evidence of real losses suffered by the plaintiff. The findings of this research are expected to be a consideration, especially for judges in the Religious Courts who handle sharia economic disputes. Judges are expected to explore the legal aspects and sharia principles completely so that the resulting decisions reflect justice, certainty, and expediency while still based on sharia principles.